Confocal Raman Microscopy for the Analysis of the Three-Dimensional Shape of Polymeric Microsphere Layers. Issue 6 (June 2022) - Syring, Alina; Wang, Zunhao; Molle, Julia; Keese, Hendrik; Wundrack, Stefan; Stosch, Rainer; Voss, Tobias
The reconstruction of the three-dimensional (3D) morphology of polymeric microsphere layers based on confocal Raman microscopy was studied. Refraction of the Raman laser beam at the curved surface of the spheres broadens the focus volume inside the sphere. Compared to planar layers, the focus gets trapped inside the spheres such that the measured depth profiles are shifted and broadened. Additionally, the Raman signal of the underlying substrate is already observed for nominal focus positions above the microsphere layer. The results are successfully modeled with ray-optical simulations that allow for a clear understanding of the relevant mechanisms that lead to the generation of the Raman signals in the complex three-dimensional structures. Graphical Abstract